Default on Capital’s Returnment Contract for Parking Business Cooperation in the Perspective of Contract Law (A Case Study of Court Decision Number 2/Pdt.G/2023/Pn Bbs) - Safitri, Fadia Rahma (Faculty of Law, Universitas Jenderal Soedirman, 2025)
An agreement creates binding commitments for the parties to fulfill its terms, and failure to do so is considered a default. In business agreements, default can occur if obligations are unmet, making a business capital return agreement essential for legal certainty. This study examines the provisions and legal consequences of default in a business capital return agreement as seen in Decision Number 2/Pdt.G/2023/PN Bbs. Using a juridical-normative approach with descriptive analytical methods, the research relies on secondary data, including primary, secondary, and tertiary legal materials analyzed qualitatively. The study reveals that default provisions are linked to three key elements: the existence of a binding agreement, the debtor’s failure to perform, and the presence of fault. In Decision Number 2/Pdt.G/2023/PN Bbs, all these elements were met. The binding aspect was established as the defendant was obligated to return Rp 60,000,000.00 in business capital to the plaintiff by September 22, 2018, as per the agreed verval term. The debtor failed to fulfill this obligation, demonstrating non-performance and delay. Fault was confirmed under Article 1238 of the Civil Code, as the defendant did not return the capital by the specified date, thus being considered negligent. The legal consequences of the default included compensation of Rp 60,000,000.00 and court costs of Rp 1,180,000.00 imposed on the defendant. This case underscores the importance of fulfilling contractual obligations to avoid legal repercussions and reinforces the role of capital return agreements in maintaining business certainty.Keywords: Business Cooperation; Capital Returnment; Default.